Antibodies against six human herpesviruses in relation to seven cancers in black South Africans: a case control study. - Berrington de González, A; Urban, M; Sitas, F; Blackburn, N; Hale, M; Patel, M; Ruff, P; Sur, R; Newton, R; Beral, V (2006)
BACKGROUND: Infections with certain human herpesviruses have been established as risk factors for some cancer types. For example, Epstein-Barr Virus is considered a cause of Burkitt's lymphoma and other immunosuppression related lymphomas, Hodgkin lymphoma, and nasopharyngeal cancer. Several other human herpesviruses have been linked to cancers but the totality of evidence is inconclusive. METHODS: We conducted a systematic sub-study from within an ongoing case control study of adult black South Africans to investigate the relationship between antibodies to six human herpesviruses and seven cancer groups that may be caused by infectious agents. Subjects had incident cancers of the oral cavity (n = 88), the cervix (n = 53), the prostate (n = 66), Hodgkin lymphoma (n = 83), non-Hodgkin lymphoma (n = 80), multiple myeloma (n = 94) or leukaemia (n = 203). For comparison, patients with other cancers (n = 95) or cardiovascular disease (n = 101) were randomly selected from within the study. Patients were interviewed and their blood was tested for IgG antibodies against HSV-1, HSV-2, VZV, EBV-EBNA, CMV and HHV-6 using enzyme linked immunosorbent assays. Because these viruses are highly prevalent in this population, optical density results from the assays were used as an indirect, quantitative measure of antibody level. RESULTS: There was significant variation in the mean log antibody measures for HSV-2, VZV, CMV and HHV-6 between the disease groups. However, none of the specific cancer groups had significantly higher mean log antibody measures for any of the viruses compared to either control group. In a more detailed examination of seven associations between cancers and herpesviruses for which there had been prior reports, two statistically significant associations were found: a decreasing risk of myeloid leukaemia and an increasing risk of oral cancer with increasing tertiles of antibodies against HHV-6 compared to all other patients (p-trend = 0.03 and 0.02, respectively). Odds ratios for the top tertile compared to the bottom tertile were 0.58 (95%CI 0.3-1.0) for myeloid leukaemia and 2.21 (95% CI 1.1-4.3) for oral cancer. CONCLUSION: In this population, using these tests for IgG, neither mean antibody measure nor high antibody measure against human herpesviruses 1-6 was strongly associated with any of the seven cancer groups. However, we may not have had sufficient power to detect weak associations or associations with a sub-type of cancer if they were present.